Hyperbaric oxygen therapy for poststroke insomnia: a systematic review and meta-analysis protocol - Rui Shi; Xingyu Chen; Wen Xue; Wenyi Meng; Zhaozheng Liu; Liping Chang; Ruozhu Lu; Yue Deng (BMJ Open)
Introduction Insomnia stands as a frequent consequence of a cerebrovascular event, afflicting a substantial fraction of those who endure the aftermath of stroke. The ramifications of insomnia following a stroke can further exacerbate cognitive and behavioural anomalies while hindering the process of neurological convalescence. While several randomised controlled trials (RCTs) have scrutinised the effects of hyperbaric oxygen therapy (HBOT) on poststroke insomnia, the advantages and drawbacks persist in a state of ambiguity. We advocate for a systematic review and meta-analysis of randomised clinical trials to comprehensively evaluate the effectiveness and safety of HBOT in the context of poststroke insomnia.Methods and analysis A systematic search will be conducted from nine major databases (PubMed, Web of Science, EMBASE, VIP Information Database, Cochrane Central Register of Controlled Trials, China National Knowledge Infrastructure, China Biomedical Literature Database and Wanfang Database, Physiotherapy Evidence Database (PEDro)) for HBOT for poststroke insomnia of RCTs. The search procedures will adhere to a rigorous approach, commencing from the inception date of each database and continuing until 1 November 2023, with inquiries conducted exclusively in English and Chinese. The primary outcome will focus on the alteration in the quality of sleep while secondary outcomes will encompass the evaluation of adverse events and the rate of reoccurrence. The process of selecting studies, extracting data and evaluating the quality of research will be carried out independently by two reviewers. The quality of the included literature will be assessed using the tools of the Cochrane Collaboration. Meta-analysis will be performed by using RevMan V.5.4 and STATA V.16.0.b software. Finally, the quality of evidence will be assessed using the Grading of Recommendations, Assessment, Development and Evaluation method.Ethics and dissemination As all data are derived from published investigations via databases without direct patient contact, ethical approval is obviated in this study. The scientific studies will be published in professional academic publications.PROSPERO registration number CRD42023468442.